SOSIALISASI DAN EDUKASI DALAM MENEKAN ANGKA PERKAWINAN DINI DI INDRAMAYU - Hadiati, Mia; Mingga, Britney Wilhelmina Berlian; Tansir, Charisse Evania (Jurnal Serina Abdimas, 2025)
Early marriage in Indonesia, particularly in Indramayu Regency, is a pressing social issue that requires addressing. Although Law Number 1 of 1974 and its revision through Law Number 16 of 2019 set the minimum age for marriage at 19, the practice of underage marriage remains widespread. Data shows that in 2023, there were 425 cases of early marriage in Indramayu, with the main factors being premarital pregnancy and parental pressure. The consequences of early marriage are devastating, both in terms of health, education, and socioeconomics, potentially exacerbating the cycle of poverty. Therefore, efforts to address early marriage through community outreach and education are crucial. The implementation method for this community service includes several stages, starting from preparation, proposal development, activity planning, to implementation of outreach and final report preparation. The outreach activities are designed to raise legal awareness in the community, including education regarding the marriage age requirements stipulated in the law and preventive measures that can be taken early on. The implementation of socialization and education activities to reduce the number of early marriages in Indramayu has created an understanding of the negative impacts of underage marriage, as well as legal awareness for the people of Indramayu Regency, and educated the importance of cooperation between society, religion, and the government in jointly making Indonesia a success without underage marriage. Perkawinan dini di Indonesia, khususnya di Kabupaten Indramayu, menjadi isu sosial yang mendesak untuk ditangani. Meskipun Undang-Undang Nomor 1 Tahun 1974 dan revisinya melalui Undang-Undang Nomor 16 Tahun 2019 menetapkan batas usia minimal menikah pada 19 tahun, praktik perkawinan di bawah umur masih marak terjadi. Data menunjukkan bahwa pada tahun 2023, terdapat 425 kasus perkawinan dini di Indramayu, dengan faktor utama seperti kehamilan di luar nikah dan desakan orang tua. Konsekuensi dari perkawinan dini sangat merugikan, baik dari segi kesehatan, pendidikan, maupun sosial ekonomi, yang berpotensi memperburuk siklus kemiskinan. Oleh karena itu, upaya penanggulangan perkawinan dini melalui sosialisasi dan edukasi kepada masyarakat menjadi sangat penting. Metode pelaksanaan pengabdian kepada masyarakat ini meliputi beberapa tahap, mulai dari persiapan, penyusunan proposal, pembuatan rencana kegiatan, hingga pelaksanaan sosialisasi dan penyusunan laporan akhir. Kegiatan sosialisasi dirancang untuk meningkatkan kesadaran hukum bagi masyarakat, didalamnya memuat edukasi mengenai syarat usia menikah dalam Undang-Undang, dan pencegahan-pencegahan yang dapat dilakukan sejak dini. Terlaksananya kegiatan sosialisasi dan edukasi dalam menekan angka perkawinan dini di Indramayu telah mewujudkan pemahaman akan dampak negatif dari perkawinan anak dibawah umur, serta kesadaran hukum bagi masyarakat Kabupaten Indramayu, dan mengedukasi pentingnya kerja sama akan masyarakat, agama, dan pemerintah dalam bersama menyukseskan Indonesia tanpa perkawinan anak dibawah umur.